The Empty Child: Dystopian Innocence and Samuel Delany’s Hogg - Jonathan Mitchell (European Journal of American Studies)
This essay examines Samuel Delany’s novel, Hogg to interrogate the figure of the innocent child and the role of the family in America, especially in mid-century America. The essay contends that the novel, narrated by the unnamed eleven-year-old protagonist who details both his polymorphously perverse sexual exploits as companion to the eponymous Hogg (outcast, murderer and rapist for hire) and acts also as chronicle of Hogg’s experiences over 72 hours, destabilizes the ideology of innocence that acts as a utopian foundation to America’s national understanding of itself as exceptional.